EVALUASI TATA KELOLA TEKNOLOGI INFORMASI DENGAN MENGGUNAKAN COBIT 4.0 DOMAIN DS (DELIVERY AND SUPPORT) DAN ME (MONITORING AND EVALUATION) STUDI KASUS : PESANTREN AL HIDAYAH BOARDING SCHOOL - Rani Irma Handayani (Jurnal Techno Nusa Mandiri, 2013)
Modeling management of Information Technology (IT) is specific in accordance with the company's strategy and goals. In this study presented a draft model of IT management for Al Hidayah Islamic Boarding School by using the COBIT framework (Control Objectives for Information and Related Technology) version 4.0 in the domain Delivery Support (DS) Monitoring and Evaluation (ME). The design of the model is adapted to the characteristics of the business strategy and objectives of Al Hidayah Islamic Boarding School and is expected to be a reference in the management of IT at Al Hidayah Islamic Boarding School and other schools. Methodology through an interim analysis of the identification of the vision, mission, and goals of the school organization. Next step is the identification of management awareness of the functions of its IT assets in support of the achievement of the vision and mission of the company through a questionnaire. From both these data, it can be determined the target maturity (expected maturity level) corresponding to Al Hidayah Islamic Boarding School. Then proceed with assessing the current maturity level through questionnaires and interviews with the respondents related to the management of IT. A follow-up to be being done is by doing recommendation at 16 control objectives at domain DS (Delivery Support) that is DS1, DS2, DS3 up to DS13 and 4 control objectives at domain ME (Monitoring Evaluation) that is ME1, ME2, ME3 & ME4